MEMBANGUN RELASI : ETIKA PERSAHABATAN DALAM PERSPEKTIF ARISTOTELES - Yohanes Probo Dwi (Psibernetika, 2016)
In Building a relationship with the environment and place of residence, people needother people who are called as friends. A friend in the perspective of Aristoteles issomeone who is believed to help humans in order to fulfill their needs. ThereforeAristoteles divides friendship in the three group, that friendship is built on the basis of mutual benefit. Friendship built on mutual enjoy and lastly knit friendship based on mutual love or love. Besides, Aristoteles sought so that fiendship to be nurturedcontinuously. This friendship must be on the level mutual developing personal abilities of each so that more and hone skills and skills with each other. Keyword: Relatinship, friendship, Perspektive, Aristoteles.